Los acuerdos atributivos de jurisdicción en Derecho Procesal Civil Internacional español - Garau Sobrino, Federico F. (CUADERNOS DE DERECHO TRANSNACIONAL, 2010)
Jurisdiction agreements are contracts on procedural relationships. Therefore, their analysis from the perspective of the International Civil Procedural Law requires the fragmentation of each one of the elements that makes up the agreement. Thus, civil matters, so as the existence and validity of the agreement, will be governed by the law designated by the conflict of laws rules on contractual obligations. On the other hand, purely procedural aspects (eligibility, form and effects) shall be complied with the lex fori. In order to develop a detailed landscape of the agreements regulation in the Spanish Legal System, this paper analyses the European Union rules (Brussels I Regulation and Lugano Convention) and the internal ones (Judiciary Act and some other Spanish legislation related to this subject). All this is complemented with the study of case-law of the Court of Justice of the European Union on Community Legislation, so as these of the Spanish courts.